RUBIKS CUBE ALGORITHM - PROF. S. G. SANMUKH; MR. SOMAYYA S. AVADUT (International Journal of Innovations in Engineering Research and Technology, 2021)
The Rubik’s Cube is a 3-D mechanical puzzleoriginally called the“Magic Cube”.Invited in 1974 by Erno Rubik. He is a Hungarian inventor, architect and professor of architecture. Rubik cube is mind game. This game is very interesting and smartness game,this game is won the German game of the year.This game’s aim is all the same colors are in one said then the game is complete.